The Precursors of Reading Ability in Young Readers: Evidence From a Four-Year Longitudinal Study - Oakhill, Jane V.; Cain, Kate (Scientific studies of reading, 2012)
We report a longitudinal study investigating the predictors of reading comprehension and word reading accuracy between the ages of 7 to 8 (UK Year 3) and 10 to 11 years (Year 6). We found that different skills predicted the development of each. Reading comprehension skill measured in Year 3 was a strong predictor of comprehension in Year 6; vocabulary and verbal IQ also made significant unique contributions to the prediction of comprehension ability across time. Three comprehension components (inference, comprehension monitoring, and knowledge and use of story structure) emerged as distinct predictors of reading comprehension in Year 6, even after the autoregressive effect of comprehension was controlled. For word reading accuracy, early measures of word reading accuracy and phonemic awareness predicted later performance.